The inhibition of PAI-1 for restoration of skeletal muscle and skin repair in diabetes mellitus - Rebalka, Irena Alexandra (My University, 2017)
Type 1 diabetic (T1D) individuals are burdened with many systemic complications, including impairments in skeletal muscle and cutaneous repair following injury. Plasminogen activator inhibitor 1 (PAI-1), the primary inhibitor of the fibrinolytic system, plays a critical role in the regulation and progression of tissue repair via controlling both extracellular matrix breakdown and cell migration. Previous work has demonstrated that elevations in PAI-1 inhibit adequate tissue regeneration, and has shown that PAI-1 is overexpressed in T1D patients regardless of insulin therapy. As such, the purpose of this thesis is to investigate the effects of known PAI-1 inhibitors on tissue repair of skin and skeletal muscle in T1D. To undertake these experiments, a rodent model of T1D was used, and animals were subject to cutaneous and skeletal muscle injuries. PAI-039, a small-molecule PAI-1 inhibitor, and Fluvastatin, a readily available statin that, among other functions, is known to inhibit PAI-1, were administered, and their effects on tissue regeneration were examined. PAI-039 was effective in restoring cutaneous wound closure in T1D. Fluvastatin, on the other hand, not only proved deleterious to both cutaneous and skeletal muscle regeneration, but also caused a pathological change in lipid deposition in the diabetic rodents. Overall, PAI-1 inhibition via a therapeutic agent that has a multitude of other pleiotropic effects is not recommended for improving T1D tissue repair. PAI-1 inhibition via a specific small-molecule inhibitor does, however, prove beneficial to cutaneous regeneration. Taken together, this data lays the foundation for future studies investigating small-molecule PAI-1 inhibitors as a therapeutic for the restoration of tissue repair in T1D.